MAP OUT A NEW HISTORICAL TRAJECTORY OF ISLAM NUSANTARA - Bizawie, Zainul Milal (INC- Islam Nusantara Center, 2018)
In the discourse of Islamic Nusantara, in order to obtain theoretical significance required the framework of network mapping, the transmission of ideology and culture, and genealogy of knowledge. network mapping becomes the foundation of the tracking of figures, subjects and agencies, in this case scholars, kiai and santri as the chain of the process of disseminating values ​​that carried Islam Nusantara. While the transmission of ideology becomes the backbone of the epistemic framework in the Islamic Nusantara reason. Islam Nusantara is a process of traditional dialectic, the result of the crossing of various Islamic universal thoughts. therefore, a methodological framework is required in tracking the genealogy of knowledge, which will become the main basis for assembling the common thread, the common point and objective of Islamic transmission to the archipelago. by tracing genealogy, will emerge pattern, pattern and structure of the science contained by Islamic tradition of archipelago. in this context, this paper seeks to offer alternative methodology to compile historical trajectory which will facilitate the observers and activists of Nusantara Islam in connecting and or grafting various local history narratives as well as finding local wisdom within answer the various contexts and the surrounding diversity. The method rests on the significance of sanad theory and social networking in the course of the relationships of the perpetrators of history that surround it. with narrative continuity, diversity in context, and horizon of facts with accurate and speculative analysis that can be accounted for, it will enrich the historic treasures of the archipelago and is useful for building a friendly, moderate, tolerant and contextual Islamic facewith its times ..